"I always walked out with an empty purse." Older adults' engagement with electronic gambling machines in Victoria, Australia. (1st July 2021) - Pitt, Hannah; Thomas, Samantha L.; Cowlishaw, Sean; Randle, Melanie; Balandin, Susan
Abstract: Issue addressed: Older adults are at an increased risk of experiencing gambling harm, which may be due to their use of high‐intensity gambling products such as electronic gambling machines (EGMs). However, little research has explored the motivations behind older adults' engagement with EGMs, their understanding of the structural characteristics of EGMs, or their perceptions of risk associated with EGM gambling. This paper aims to address this gap in the literature. Methods: Focus groups were conducted in Melbourne, Australia with n = 126 adults aged 55+, who had attended a club or pub in the last 12 months. Topics included EGM attitudes and behaviours, structural characteristics of EGMs, and the potential risks associated with EGM gambling. Thematic analysis was used to interpret the data. Results: For most participants, EGM gambling was secondary to their participation in other activities available within venues. Participants identified structural characteristics of EGMs; however, there were some misconceptions about how EGMs operated, including how or why machines paid out. Most participants perceived that they were not at risk of gambling harm because they engaged in "responsible" gambling practices such as setting limits. Conclusions: Older adults often engaged in EGM gambling because of its availability in community‐based venues. Older adults' perception that they are implementing responsible gambling practices may be increasing their susceptibility to harm. So what?: There is a need to reduce the availability and accessibility of EGMs in community settings and develop public education programs that are tailored to the needs of older adults.